FACTORS THAT INFLUENCE SURVIVAL RATE IN EXTRAOCULAR RETINOBLASTOMA PATIENTS AT CIPTO MANGUNKUSUMO HOSPITAL : 2018 - Aprina, Dwie; Barliana, Julie Dewi; Yulia, Dian Estu; Sitorus, Rita Sita (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2024)
Introduction: Optimal therapeutic approach for extraocular retinoblastoma has not been determined. The prognosis of extraocular retinoblastoma compared with intraocular retinoblastoma remains relatively poor. The aim of our study is to describe the factors that influence the survival rate of extraocular retinoblastoma. Methods: A retrospective study. Patients diagnosed with extraocular retinoblastoma in Cipto Mangunkusumo Hospital, within 1 January to 31 December 2018 were reviewed for patient and tumor characteristic, ocular management, and patient survival. Result: During the study period, a total of 80 patients were diagnosed with retinoblastoma in our center, 41.2% had an extra-ocular extension The mean age at diagnosis was 25.57 months, with 56.7% being males. Leukocoria is the initial sign most often noticed by parents. The median lag period was 12 months. Neoadjuvant chemotherapy was performed in 96.7% of cases, that carried out an average of 3-4 cycles before enucleation/exenteration. At the end of September 2019, there were 17 deaths in our study. Overall survival was 19.82 months with a mean age of 27.6 months, whereas extraocular death time ranged from 4 months to 55 months. Conclusion: Death was more common in patients with age at first symptom less than 24 months, bilateral retinoblastoma, lag period more than 12 months, advanced stage (IVB) and delayed therapy after proptosis more than 3 months.